Hubungan antara Literasi Kesehatan dengan Mekanisme Koping pada Lansia dengan Hipertensi - Nana Lia Safitri; Lita Heni Kusumawardani; Arif Imam Hidayat (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Introduction: Age in the elderly who are getting older are more at risk of developing hypertension. The efforts of the elderly in dealing with hypertension form a coping mechanism that is influenced by health literacy in managing hypertension control. Objectives: Â This study aims to determine the relationship between health literacy and coping mechanisms in the elderly with hypertension. Methods: This type of research is cross sectional, the sample is taken using total random sampling with a total of 126 elderly people aged 60 years. The research instrument used a questionnaire. The analysis test used the Spearman Rank correlation test. Results: The results of this study include demographic data including age, gender, education, disease history, income, and blood pressure. The results of the univariate analysis on the health literacy variable, namely the elderly are included in the category of adequate health literacy with a median value of 36.00, and a minimum and maximum value range of 13 to 48. The elderly coping mechanism variable is included in the category of adaptive coping mechanisms with a mean score. of 53.57 and the standard deviation of 5.550. The correlation test in this study have a significant relationship with p value = 0.037 with a coefficient value of 0.186. Conclusions: Â Health literacy have a significant relationship with coping mechanisms in the elderly with hypertension, but it is very weak.